An unusual new species of Trechona (Araneae: Mygalomorphae: Dipluridae), from quartzitic caves of the Diamantina Plateau, Minas Gerais, Brazil, with a key to the known species - Guadanucci, Jose Paulo L. [UNESP]; Fonseca-Ferreira, Rafael; Cerqueira Baptista, Renner Luiz; Pedroso, Denis Rafael (Taylor & Francis Ltd, 2016)
Trechona diamantina sp. nov. is described from quartzite caves in Diamantina, central Minas Gerais State, Brazil. This represents the largest cavernicolous mygalomorph population ever recorded. The new species is the first Trechona recorded from a xeric habitat, namely the Rocky Fields on the Diamantina Plateau. T. diamantina sp. nov. is closely related to T. uniformis, both species possessing elongated male and female copulatory organs and both constructing distinct funnel-webs and sheet-webs in quartzite formations. T. diamantina sp. nov. is distinct in possessing less elongated embolus and receptacula seminis. A key for all valid species of the genus is given.
Keywords: Spider; new species; taxonomy; troglophile; hypogean environment